2012
DOI: 10.1016/j.neuropsychologia.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Subjective cognitive complaints and amyloid burden in cognitively normal older individuals

Abstract: Accumulating evidence suggests that subjective cognitive complaints (SCC) may indicate subtle cognitive decline characteristic of individuals with preclinical Alzheimer’s disease (AD). In this study, we sought to build upon previous studies by associating SCC and amyloid-β deposition using Positron Emission Tomography with Pittsburg Compound B (PiB-PET) in cognitively normal older individuals. One-hundred thirty one subjects (mean age 73.5 ± 6) were administered three subjective cognitive questionnaires and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
332
8
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 418 publications
(380 citation statements)
references
References 64 publications
33
332
8
7
Order By: Relevance
“…Moreover, the presence of amyloid brain lesions was associated with a low cognitive awareness in our participants. 34 This result may appear in contradiction with some recent data 56 but it is noteworthy that the subjects were only complainers and did not fully correspond to the definition of subjective cognitive decline 57 . However, an extensive investigation of their subjective feelings was performed, and to our knowledge, INSIGHT-preAD is the first study with such a comprehensive evaluation of different aspects of cognitive complaints, including 6 questionnaires with a total of 88 items all of which administered with the same investigators in participants who were cognitively healthy at study entry.…”
Section: Discussioncontrasting
confidence: 91%
“…Moreover, the presence of amyloid brain lesions was associated with a low cognitive awareness in our participants. 34 This result may appear in contradiction with some recent data 56 but it is noteworthy that the subjects were only complainers and did not fully correspond to the definition of subjective cognitive decline 57 . However, an extensive investigation of their subjective feelings was performed, and to our knowledge, INSIGHT-preAD is the first study with such a comprehensive evaluation of different aspects of cognitive complaints, including 6 questionnaires with a total of 88 items all of which administered with the same investigators in participants who were cognitively healthy at study entry.…”
Section: Discussioncontrasting
confidence: 91%
“…Recent research correlates the presence of SMC and biomarkers including brain region volumes, [24][25][26] amyloid burden, 26 brain atrophy, 9 and gray matter atrophy, 27 and is consistent with earlier neuropathologic reports. 13,28 In this study, neuropathology was obtained on a large proportion of participants who died.…”
Section: 6supporting
confidence: 87%
“…by guest on May 10, 2018 http://stroke.ahajournals.org/ Downloaded from same study, no association was found between objective memory measures and amyloid burden. 31 Thus, the deposition of amyloid-β proteins in the vessels of the brain can compromise their integrity, which may lead to leakage and subsequently contribute to clinical stroke. 32 We found that the association between subjective memory complaints and stroke was strongest in highly educated persons.…”
Section: Discussionmentioning
confidence: 99%